Full panorama images of 17 field plot centres during the expedition to the Buor Khaya Peninsula, Northern Yakutia, summer 2014 - Kruse, Stefan (PANGAEA, 2025)
During an expedition to northern Yakutia in summer 2014, full panoramic images of the sampled vegetation plots were captured for documentation purposes. The images were taken with a standard camera (Nikon Coolpix P7000) from the centre of the vegetation plots. At each, multiple rows of images in all directions were recorded holding the camera at a fixed position at breast height (1.3 m above ground). The images were stitched in Autopano Giga 4 (Kolor) and humans or other artificial objects masked if possible. Blended images were exported to 360x180 panorama images (10000x5000). The panorama image was manually checked for gaps or human shadow errors which were healed with GIMP resynthesizer plugin (https://github.com/bootchk/resynthesizer).